2014
DOI: 10.1186/1475-2875-13-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimating malaria parasite density among pregnant women at central Sudan using actual and assumed white blood cell count

Abstract: BackgroundMicroscopic examination using Giemsa-stained thick blood films remains the reference standard for detection of malaria parasites and it is the only method that is widely and practically available for quantifying malaria parasite density. There are few published data (there was no study during pregnancy) investigating the parasite density (ratio of counted parasites within a given number of microscopic fields against counted white blood cells (WBCs) using actual number of WBCs.MethodsParasitaemia was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…In patient populations of exclusively or mostly children under five years, it has been documented that the recommended WBC count 8,000 cells/µl either was appropriate (Laman et al, 2014) or in a rare case underestimated parasite densities (Adu-Gyasi et al, 2012). In contrast, in populations consisting of mostly adults, this assumed WBC value would lead to significant overestimates of parasite densities (Alves-Junior et al, 2014; Haggaz et al, 2014; Jeremiah and Uko, 2007; McKenzie et al, 2005; Rodriguez-Morales et al, 2005; Tangpukdee et al, 2008). Taken together, the WHO recommend WBC value of 8000 cells/µl, based on a study cohort that was nearly 50% under the age of five, may have inflated the WBC counts in a population consisting of mostly adults (Dowling and Shute, 1966).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patient populations of exclusively or mostly children under five years, it has been documented that the recommended WBC count 8,000 cells/µl either was appropriate (Laman et al, 2014) or in a rare case underestimated parasite densities (Adu-Gyasi et al, 2012). In contrast, in populations consisting of mostly adults, this assumed WBC value would lead to significant overestimates of parasite densities (Alves-Junior et al, 2014; Haggaz et al, 2014; Jeremiah and Uko, 2007; McKenzie et al, 2005; Rodriguez-Morales et al, 2005; Tangpukdee et al, 2008). Taken together, the WHO recommend WBC value of 8000 cells/µl, based on a study cohort that was nearly 50% under the age of five, may have inflated the WBC counts in a population consisting of mostly adults (Dowling and Shute, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Since the abundance of WBCs is influenced by the host immune status (Berens-Riha et al, 2014), and may vary in people of different races, ages, nutritional conditions, and pathogen infections, the baseline values of leukocytes in patients may differ significantly between populations and geographical regions (Bain, 1996). Therefore, it has been suggested that the best solution for estimating parasite densities is to use different WBC counts for different geographical regions, age groups and sub-populations (e.g., pregnant women), and epidemiological settings (Adu-Gyasi et al, 2012; Alves-Junior et al, 2014; Haggaz et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, there have been a few studies substantiating the inapplicability of assumed TLC of 8,000/μL in both adult and child populations. In adults, older children and pregnancy, assumed TLC of 8,000/μL has been found to result in significant overestimation of PI, whereas in younger adults it results in marked underestimation [ 5 - 7 , 13 ]. Thus, in view of the current study and others, it is advisable to abstain using assumed TLC of 8,000/μL for the calculation of PI by microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…For parasite density determination, the number of asexual parasites was counted against 200 leucocytes, where an average leucocytes count of 8000/μL was assumed. The blood smear was considered negative when 200 high power fields had been examined without visible parasite [ 22 ].…”
Section: Methodsmentioning
confidence: 99%